2020
DOI: 10.11591/ijeecs.v20.i2.pp932-938
|View full text |Cite
|
Sign up to set email alerts
|

Development of mobile application for Malay translated hadith search engine

Abstract: This paper presents the development of mobile application for Malay Translated Hadith search engine. Limitations of current Hadith web application are the design is to optimize its usage on desktop computer but not on mobile devices, which requires simple and user friendly interface. Besides that, web application also needs internet connection to use. Due to increase usage of mobile application among mobile phone users, many existing web applications have moved to mobile based applications to cater for increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…According to [18] there are three ways for converting terms into vector namely term frequency, term occurrences and TF-IDF. TF-IDF is a weighing factor that can be used to replace binary and word count representation [25]. Conversion of term to vector produce a lower weightage to irrelevant terms while a higher weightage to the relevant terms with vector value of 0 and 1 respectively.…”
Section: Methodsmentioning
confidence: 99%
“…According to [18] there are three ways for converting terms into vector namely term frequency, term occurrences and TF-IDF. TF-IDF is a weighing factor that can be used to replace binary and word count representation [25]. Conversion of term to vector produce a lower weightage to irrelevant terms while a higher weightage to the relevant terms with vector value of 0 and 1 respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Also, Seghiri and Belguidoum [13] and Kadhim and Gaata [14] shows that several companies work on the internet to collect personal data and use it to make a profit. A study by Unger [15] discuss that based on the evaluation security process of nine IM applications that have done, the results confirm that most of these applications have major security flaws, which make them prone to various kinds of attacks [16], [17]. Moreover, an article has done by two researchers revealed that IM server owners could access the personal data of their customers when they want [18].…”
Section: Introductionmentioning
confidence: 96%
“…Some of time-critical weather alert apps [7], investigate the UI design principles of mobile Al-Quran apps for senior citizens [8], the design and usability quality metrics evaluation of chromatin immunoprecipitation combined with sequencing (ChIP-seq) web tools [9], a new prototype design for a smartwatch UI [10], the development of a mobile-based UI that makes it easier for farmers to view the data [11], redesigning food delivery application [12], and development of Marine tourism [13]. In the education sector [14][16], among others design and development of a simple content management system for learning called the EMasters [17], PAUD monitoring application [18]. In the health sector there are several studies [19][21], including developed of the healthy phone is a mobile medical emergency call apps that can help people with hearing impaired when in emergency situations [22].…”
Section: Introductionmentioning
confidence: 99%